The Influence of Entrepreneurial Literacy and Digital Literacy on Business Success Through Digital Platforms as a Mediating Variable Among Metal Artisans in Makassar City - Mustari, Mustari; Purnama, Widia; Ahmad, M. Ihsan Said; Ampa, Andi Tenri (International Journal of Contemporary Sciences (IJCS), 2025)
This study aims to examine the influence of Entrepreneurial Literacy and Digital Literacy on business success, with Digital Platforms serving as a mediating variable, among metal artisans in Makassar City. A quantitative research method with a descriptive approach was applied, using a sample of 150 metal craftsmen. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The results indicate that both Entrepreneurial Literacy and Digital Literacy significantly and positively affect the business success of metal artisans, with Digital Platforms acting as a mediator in this relationship. The study underscores the importance of these factors in fostering business growth. Based on these findings, it is recommended that government authorities intensify efforts to increase awareness and promote entrepreneurial and digital literacy, helping business owners enhance their financial management, entrepreneurial skills, and ability to effectively utilize digital platforms for marketing their products.